(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2023)
A comprehensive clinical and instrumental, laboratory, psychovegetative examination of 139 patients with cirrhosis of the liver of various etiologies (viral, alcoholic, combined) and severity according to Child-Pugh was carried out. The comparison group was represented by 104 patients with chronic hepatitis of viral, alcoholic and combined etiology. The control group consisted of 30 healthy people, comparable in gender and age. In patients with cirrhosis of the liver, as well as in patients with chronic hepatitis, emotionally labile, neurotic traits and high personal anxiety prevailed. The tendency to sympathicotonia depended on the severity of liver damage. The predominance of tone and reactivity of the sympathetic part of the autonomic nervous system is a compensatory enhancement of adaptive mechanisms.